Valuation of Waste Oil Palm Biomass for Energy in Palm Oil Mill in Indonesia - Armansyah Halomoan Tambunan (International Journal of Oil Palm, 2019)
Valuation of biomass and its waste is indispensable for sustainable development of bioenergy in Indonesia. The objective of this research is to estimate the value of biomass, mainly from oil palm waste, for supporting bioenergy development in Indonesia. The research was applying thermodynamic theory to reinterpret the economic valuation by exergonomic analysis on biomass conversion to electricity. The results revealed that exergonomic value of electricity generated from oil palm fiber was 5 cents USD kWh-1, while the steam was 0.46 cents US kWh-1, under the assumption of zero biomass value. When the value of electricity was at its production base cost, the biomass (i.e. oil palm fiber) could be valuated to Rp 296.57 per kWh of its exergy content, or Rp 1 764.73 kg-1 of the biomass. The real price of shell in the field was Rp 700 kg-1. The results show that either the oil palm fiber is undervalued or the production cost of electricity generated from the fiber could be lower.